Analisis Pengaruh Penggunaan Uang Elektronik terhadap Perilaku Konsumtif di Kalangan Mahasiswa - Ajeng Ayu Pratiwi (Asosiasi Ahli Administrasi Indonesia, 2022)
The purpose of this research is to find out and analyze the influence of the use of electronic money on the consumptive behavior of students. The research method used is descriptive quantitative. The population in this study were all active students at the Bandung State Polytechnic. The data collection technique was carried out by distributing questionnaires to 108 respondents. The analytical method used is simple regression analysis and validity test, reliability test, and normality test. The results of the study show that the use of electronic money influences consumptive attitudes among Bandung State Polytechnic students. The use of electronic money contributes 10.8% to the consumptive attitude of Bandung State Polytechnic students.